Website Characteristics on Customer Satisfaction - Supriyati; S P Harahap (Journal of Business and Behavioural Entrepreneurship, 2021)
The purpose of this research is to find out how customer satisfaction in the field of online business. The research method used was descriptive qualitative research method. A descriptive qualitative method is a method used to describe or analyze the results of the research. Website characteristics are defined as attributes that consumers consider when evaluating an online site. Website characteristics are measured using five dimensions shopping convenience, design, informative, security, communication. Online business is an important tool for consumers to find products, the purchase intention of consumers through online stores tends to be high. Consumer satisfaction is greatly influenced by the transaction process and trust. And, based on the result of the research, that ease, security, site design, informative and communication as well as features of an online business affect customer satisfaction.